PERAN SENI KRIYA DI ERA PERDAGANGAN GLOBAL - Timbul Raharjo (Ars: Jurnal Seni Rupa dan Desain, 2009)
In contrast to the kriyawan that able to develop aspects of research and development, innovation capability is actually a manifestation of the economics of proximity, but the producers are faced with the internal weakness of the pattern of financing and Research & Development activities and vulnerabilities to access sources of information. As a result, the role kriyawan become very important in order to encourage innovation capabilities. Proximity craftsmen with external forces such as consumers, distributors, suppliers, and competitors are considered important as a source of useful knowledge in the development of innovation capabilities for the kriyawan. Given the almost certainly composed of international trade in the export trade activities set forth many products related to art craft products. The nature of the mass and economies become one of skill in the art strength exploring the times. Indonesia has a good chance giving the art to craft to surface with high strength locality. Because of the economic nature of art is playing activity continues to craft art craft though. For that work patterns between pekriya and craftsmen sought in the form of mutual cooperation. A kriyawan work to gave birth to a product work can communicate inner experiences were also able to inspire a work product that penetrated into the sphere of mass products as art handicraft items. Of course collaboration among related subjects and aspects of the Art business cannot require each other synergistically. Selfishness in the rights and obligations differentiate cannot be synergized carefully. A product that created by kriyawan expected not to stand alone but can be used by craftsmen in a way giving royalties.Keywords: Art craft, globalization